Landscape structure shapes the diversity of plant reproductive traits in agricultural landscapes in the Brazilian Cerrado - Martello, Felipe; dos Santos, Juliana Silveira [UNESP]; Silva-Neto, Carlos M.; Cássia-Silva, Cibele; Siqueira, Karoline Nascimento; Ataíde, Marcos Vinicius Rezende de; Ribeiro, Milton Cezar [UNESP]; Collevatti, Rosane Garcia (Elsevier, 2023)
The replacement of native vegetation by crops and pasturelands compromises the functional diversity of plants and negatively influence ecosystem functions such as pollination and seed dispersal. Here, we investigate the effects of landscape structure on the diversity of functional traits in agricultural landscapes in the Brazilian Cerrado. We sampled the woody plant community in 49 sites in forests and savannas, and analyzed the density and richness of pollination and seed dispersal syndromes. We performed model selection using Akaike Information Criterion to test whether landscape variables such as habitat amount, percentage of agriculture and pasture, patch and edge densities, and compositional heterogeneity at different spatial scales influence the density and richness of woody plant functional traits related to seed dispersal and pollination syndromes. The amount of forest and patch density were the landscape predictors that explained most of the diversity of plant functional traits. The amount of agricultural and savanna as well as edge density and landscape heterogeneity also affected functional traits. Our results suggest that habitat amount and configuration in the landscapes drive the diversity of functional traits, pointing that maintaining habitats within Cerrado agricultural landscapes is determinant for the plant's functional traits diversity. Furthermore, a heterogeneous mosaic may favor the density or richness of plants pollinated by insects and hummingbirds. The continuous loss and fragmentation of habitats may lead to loss of ecological functions compromising the provision of ecosystems services in agricultural landscapes in the Cerrado ecoregion.
Keywords: Agroecosystems; Ecosystem function; Functional diversity; Plant reproductive traits; Savanna; Seasonally dry tropical forests